Customer loyalty: a systematic literature review and future directions in the Islamic Financial Industry - Reem Abdulrahman Alfaisaly (Cogent Business & Management, 2024)
Customer loyalty has become a real concern in the Islamic finance industry, instigating a comprehensive review of studies on this topic. Thus, this study presents a systematic literature review on customer loyalty in the context of the Islamic finance industry. Consequently, 40 research articles were reviewed and several factors influencing customer loyalty were identified. The results show that variables such responsibility (CSR), service quality, credibility, satisfaction, religiosity, financial and spiritual advantages, image, trust, and close customer relationships directly and indirectly influence customer loyalty in the Islamic finance industry. Additionally, social exchange theory is widely used in this area of research. The data trends also show that research in this field has intensified over time with a requisite for future research in several dimensions. This study proposes future research directions in light of these shortcomings. Additionally, this study contributes to the domain of Islamic finance, with a special focus on customer loyalty with the incorporation of contemporary lens of research studies.
Keywords: 650; Customer loyalty; islamic finance; social exchange theory